Answer: (x = 6, y = -0.5)
Explanation:
Substitute into one of the equations: 3(5 - 2y) + 2y = 17
Apply Multiplicative Distribution Law: 15 - 6y + 2y = 17
Rearrange unknown terms to the left side of the equation: -6y + 2y = 17 - 15
Combine like terms: -4y = 2
Divide both sides of the equation by the coefficient of variable: y = 2 / (-4)
Remove the parentheses: y = -2 / 4
Calculate the product or quotient: y = -0.5
Substitute into one of the equations: x = 5 - 2 * (-0.5)
Remove the parentheses: x = 5 - 2 * -0.5
Calculate the product or quotient: x = 5 + 1
Calculate the sum or difference: x = 6
The solution of the system is: {x = 6, y = -0.5}
Hope this helps!